2D multilayered perovskites based on 4-chlorophenylethylamine for solar cell application. (15th January 2020) - Zhao, Wenhui; Gan, Xiaoyan; Ke, Lili; Guo, Liling; Liu, Hanxing
Highlights: A new organic cation ClC6 H4 C2 H4 NH3 + was introduced into perovskite solar cells. The grain size, crystallization and morphology of the thin films are discussed. The 2D perovskite thin films are obtained by hot-casting method. The PSC based on (CPEA)2 (MA)n−1 Pbn I3n+1 show a maximum efficiency of 11.86%. The moisture-resistant of 2D PSCs and 3D PSCs are studied. Abstract: Two-dimensional layered organic-inorganic perovskite hybrids have attracted increasing attention due to their outstanding moisture resistance and promising optoelectronic properties. However, the photovoltaic performance in solar cells is still a huge challenge for two-dimensional perovskite films. With the aim to improve the efficiency of 2D perovskite solar cells, the new (ClC6 H4 C2 H4 NH3 )2 MAn−1 Pbn I3n+1 perovskite family (abbreviated as (CPEA)2 MAn−1 Pbn I3n+1 ) are synthesized by a simple one-step hot-casting method in this study. It is found that the variation of n value (n = 3–6) has great influence on the microstructure, grain size, charge mobility, trap density and photovoltaic performance of the 2D (CPEA)2 (MA)n−1 Pbn I3n+1 . Due to the best film quality and prolonged carrier lifetime, the (CPEA)2 MA4 Pb5 I16 (n = 5) perovskite solar cell exhibits a highest efficiency of 11.86%, with a Voc of 0.989 V, a Jsc of 19.92 mA/cm 2 and FF of 60%, respectively. It is anticipated that our approach to explore new organic spacer cations in 2D perovskites may pave the way for their application with high performance.